Systemic administration of choline acetyltransferase decreases blood pressure in murine hypertension - Andrew Stiegler; Jian-Hua Li; Vivek Shah; Tea Tsaava; Aisling Tynan; Huan Yang; Yehuda Tamari; Michael Brines; Kevin J. Tracey; Sangeeta S. Chavan (BMC, 2021)
Abstract Acetylcholine (ACh) decreases blood pressure by stimulating endothelium nitric oxide-dependent vasodilation in resistance arterioles. Normal plasma contains choline acetyltransferase (ChAT) and its biosynthetic product ACh at appreciable concentrations to potentially act upon the endothelium to affect blood pressure. Recently we discovered a T-cell subset expressing ChAT (TChAT), whereby genetic ablation of ChAT in these cells produces hypertension, indicating that production of ACh by TChAT regulates blood pressure. Accordingly, we reasoned that increasing systemic ChAT concentrations might induce vasodilation and reduce blood pressure. To evaluate this possibility, recombinant ChAT was administered intraperitoneally to mice having angiotensin II-induced hypertension. This intervention significantly and dose-dependently decreased mean arterial pressure. ChAT-mediated attenuation of blood pressure was reversed by administration of the nitric oxide synthesis blocker l-nitro arginine methyl ester, indicating ChAT administration decreases blood pressure by stimulating nitic oxide dependent vasodilation, consistent with an effect of ACh on the endothelium. To prolong the half life of circulating ChAT, the molecule was modified by covalently attaching repeating units of polyethylene glycol (PEG), resulting in enzymatically active PEG-ChAT. Administration of PEG-ChAT to hypertensive mice decreased mean arterial pressure with a longer response duration when compared to ChAT. Together these findings suggest further studies are warranted on the role of ChAT in hypertension.